From Birth to Maturity: An Investigation of a Market Evolution and its Dynamics - Dass, Mayukh (Institutional Knowledge at Singapore Management University, 2010)
In this paper, we examine the internal dynamics of a market through the various stages of its evolution. Using comprehensive auction data from about 300 art auctions across about 50 auction houses over a 13 year period, we examine the behavior of market participants and its impact on multiple outcomes of interest including the price formation process and the valuation of objects and brands. Our results show that the quality of market participation changes systematically over the course of market evolution. As a consequence, the antecedents or drivers of the price formation process changes significantly over time. Implications for auction houses and investors are discussed.